Diseminasi Pengelolaan Keuangan Rumah Tangga: Perencanaan Pensiun - Farida Komalasari; Eko Ganiarto (ACADEMICS IN ACTION Journal of Community Empowerment, 2020)
This community empowerment activity is intended to improve people awareness in financial household management, especially in retirement planning.  By doing a good retirement planning, it is expected that people will have a good quality of life during their retirement.  This activity is also intended to increase households’ financial literacy.  This activity was done at Sunday, 3 November 2019 at 4-6pm, participated by 18 members of Komunitas Ibu RT 09 RW 03 Kelurahan Dukuh Kecamatan Kramat Jati Jakarta Timur.  Lecturing, true or fals, guided teaching, question & answer, simulation and discusion were used along this activity.  All participants were actively following the all program, from the beginning to the end of session.  Questions and opinions from participants show their awareness on the importance of retirement planning.  At the end of session, the participants agreed that having a good retirement planning before entering the retirement period is important.   Retirement planning is needed to reach a good wealth during the retirement.  The problem is that they do not have an enough knowledge to make a good retirement planning.   Therefore, a guidance and help are needed to increase their financial literacy, especially in composing a retirement plan.  Some topics that could be delivered to them in the future are introducing investment instruments and selecting a Financial Institution Pension Fund.